Effect of diet video-drama and telephone messages on improving parental knowledge and diet diversity of malnourished children in Kenya: A randomised controlled trial. - Beatrice C Mutai; Fredrick Were; Jalemba Aluvaala; Grace John-Stewart; E Maleche-Obimbo (PLOS Global Public Health, 2025)
Severe acute malnutrition (SAM) accounts for 1 million deaths globally each year. Ready-to-use Therapeutic Food (RUTF), recommended for treatment, is often replaced with low-nutrient home foods. We sought to determine the effect of enhanced caregiver counselling, using a dramatized video with contextualized demonstrations of local high-nutrient food (video-drama) and telephone messages on high-nutrient foods (SMS), on children's dietary diversity scores (DDS), weight gain, and caregiver knowledge. This randomised trial enrolled 213 severely malnourished children and caregivers at Mbagathi Hospital in Nairobi. Children were randomised to 3 study arms: standard of care (SOC) (children received RUTF, caregivers received routine nutrition counselling); intervention arm A (caregivers watched the video-drama at enrolment, 1- and 6-weeks post-enrolment plus SOC); and intervention arm B (caregivers received weekly SMS, watched the video-drama plus SOC). Primary outcome was DDS, secondary outcomes were weight gain and caregiver knowledge. Median DDS, mean rate of weight gain and caregiver knowledge were compared between trial arms using Kruskal-Wallis and ANOVA tests, respectively. Children's median age at enrolment was 12 months (IQR 8.0, 16.0), 50.7% were female, 74.6% were breastfeeding and 78.9% were on RUTF. Median caregiver age was 28 years (IQR 24.5, 32.0) and 98% were female. Post-intervention, children in arms A and B had significantly higher median DDS at 5 (IQR 4, 5) versus 4 (IQR 3, 5) in SOC arm (p < 0.001)]. Mean caregiver knowledge was significantly higher in arm A (4.53[±1.17)] and arm B (4.27[±1.04]) compared to 3.77(±0.91) in SOC (p < 0.001). Mean rate of weight gain was similar across study arms [7.60 g/kg/day in intervention arms, 7.30 g/kg/day for SOC (p-value 0.31)]. Video-drama enhanced SOC counselling of local high-nutrient foods, improved children's DDS and caregiver knowledge, but did not improve short-term weight gain. Weekly SMS did not provide additional benefits to the video-drama.